Legal Counseling on the Governance of Village-Owned Enterprises as a Form of Village Autonomy Independence - Firmansyah, Ade Arif; Satriawan, M. Iwan; Nurhalimah, Dewi; Malida, Reisa; Azzahra, Nabila (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This community engagement initiative stems from the persistent governance weaknesses of Village-Owned Enterprises (BUMDes), characterized by low transparency, insufficient managerial capacity, and limited understanding of the legal framework governing village enterprises. These issues hinder the effectiveness of BUMDes in achieving village economic independence.Purposes of The Devotion: The purpose of this program is to enhance the legal and managerial knowledge of village officials and BUMDes managers in accordance with existing regulations.Method of The Devotion: The method employed includes lectures, interactive discussions, and an empirical approach aimed at identifying practical challenges faced by BUMDes managers in daily operations.Results Main Findings of the Devotion: The results indicate a significant improvement in participants’ understanding of the legal foundations of BUMDes, governance mechanisms, and forms of legal accountability. Field findings reveal that BUMDes governance problems are not merely internal but are also shaped by complex licensing bureaucracy, regulatory uncertainty across ministries, weak policy support for capital participation, and psychocultural barriers such as low managerial dedication and limited entrepreneurial capacity. These combined structural and psychocultural constraints hinder BUMDes from developing as professional business entities. The program successfully increased awareness among village stakeholders regarding the importance of good governance in strengthening village economic autonomy.